Vitamin D Receptor Genetic Polymorphisms Associate With a Decreased Susceptibility to Extremity Osteomyelitis Partly by Inhibiting Macrophage Apoptosis Through Inhibition of Excessive ROS Production via VDR-Bmi1 Signaling - Zhao, Xing-Qi; Wan, Hao-Yang; He, Si-Ying; Qin, Han-Jun; Yu, Bin; Jiang, Nan (Frontiers in Physiology, 2022)
Background: Previous studies had reported that vitamin D receptor (VDR) gene polymorphisms were related to the development of several inflammatory disorders. However, potential links between such variations and the risk of developing a bone infection and underlying mechanisms remain unclear. This study aimed to analyze potential associations between VDR genetic variations and susceptibility to extremity osteomyelitis (OM) in a Chinese Han population and investigate potential mechanisms. Methods: Between January 2016 and August 2020, altogether 398 OM patients and 368 healthy controls were genotyped for six VDR gene polymorphisms, including ApaI (rs7975232), BsmI (rs1544410), FokI (rs2228570), TaqI (rs731236), GATA (rs4516035), and Cdx-2 (rs11568820) by the SNaPshot genotyping method. Then, male C57BL/6 mice were randomly divided into vitamin D–standard, –excess, –deficient, and –rescued groups. One week after making the model surgery, OM occurrence and severity were assessed using the bacterial count and histopathological staining. In vitro, phagocytosis, apoptosis, and bactericidal ability of macrophages were evaluated by overexpression or knockdown of VDR protein. Results: Significant associations were found among rs7975232, rs1544410, and OM development by the recessive model (AA vs. AC + CC, p = 0.037, OR = 0.594), homozygous model (AA vs. CC, p = 0.033, OR = 0.575), and heterozygous model (CT vs. CC, p = 0.049, OR = 0.610), respectively. Patients with the AA genotype of rs7975232 had a relatively higher mean level of vitamin D than those with AC and CC genotypes (22.5 vs. 20.7 vs. 19.0 ng/ml). Similarly, patients with CT genotype of rs1544410 had a relatively higher mean vitamin D level than those with CC genotype (20.94 vs. 19.89 ng/ml). Outcomes of in vivo experiments showed that the femoral bacterial load of vitamin D–deficient mice was highest among different vitamin D dose groups, with the most severe histopathological features of infection, and vitamin D supplementation partly reversed the changes. While in vitro experiment results revealed that active vitamin D promoted phagocytosis and sterilization of macrophages and inhibited apoptosis during infection. Reactive oxygen species (ROS) inhibitor inhibited apoptosis of macrophages induced by bacterial infection. Active vitamin D inhibited excessive ROS production in macrophages via the VDR-Bmi1 signaling pathway. Conclusion: In this Chinese cohort, ApaI and BsmI are associated with a decreased risk of OM development by influencing serological vitamin D level, the latter of which reduced macrophage apoptosis with inhibition of excessive ROS production via the VDR-Bmi1 signaling pathway.